Guide on sction research for educators / Satirah Ahmad - Ahmad, Satirah (Akademi Pengajian Bahasa, 2021)
Action Research (AR) is a research design employed collaboratively by educators to critically examine their own practice for the purpose of improvement and professional development. Due to its practicality, reflexivity and recursiveness, AR provides empowerment for educators to make necessary change in their own context. This workshop aims to highlight the AR process which begins from identifying and analysing a problem, creating an action plan, enacting the action plan, reflecting on the plan in action, reporting the findings, modifying the plan, and continuing the cycle with the revised problems. It also aims to discuss the legitimacy of AR in academic context.